(untitled) (Economics and region, 2019)
The article deals with analysis of the observations and results that point to the contrast between useful-based and resource-based approaches and the possibilities-based approach, founded by Amartya Sina (Nobel Prize in Economics in 1998). Thus, a possibilities-based approach seeks to remedy the situation by focusing on the ability to achieve specific goals rather than on the means. The nature of real existence has always been of interest to social thinkers for centuries. If the current criteria of economic progress, reflected in a number of ‘turnkey’ statistics, are orientated on the growth of inanimate "comfort objects" (such as GNP and GDP in the basis of countless economic development studies), this focus can only be justified by the impact of these objects on human lives (that they directly or indirectly affect). The interest in replacing them with direct indicators of the quality of life, well-being and freedom that people enjoy is becoming more and more apparent. The article is presented in two parts. In the first part, we will try to highlight the imperfections of traditional currency indicators, as well as the difficulties of measuring various aspects of poverty, especially in developing countries such as Morocco. We argue that poverty is not simply an idea of the inadequacy of an individual’s economic means, but rather a fundamental shortcoming that entails deprivations. The second part of the paper focuses on the reorientation of ability to explain the extent to which a possibilities-based approach could be the basis for assessing the level of financial difficulties rather than resource-focused income and wealth.